1965
DOI: 10.1080/19447026508662312
|View full text |Cite
|
Sign up to set email alerts
|

41—making–up Properties of Wool Fabrics

Abstract: The making-up properties of several wool fabrics, differing in structure and finish, have been evaluated and compared with various mechanical properties of the fabrics that were considered to govern their behaviour when they were made into a man's suit, both in the making-up process and in the subsequent life of the garment. The making-up properties were evaluated by the operatives concerned, who classified the fabrics according to the ease with which they could be handled in making-up and their appearance in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

1985
1985
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
0
8
0
1
Order By: Relevance
“…In the region of high aspect ratio (r > 3), the change in critical shear ratio caused by the change in D, and D2 is much larger than the caused by the aspect ratio, although at a smaller aspect ratio (r < 2), the change is equally significant. It is important to note that the critical shear force is related to the critical shear ratio through equation 13, which involves the specimen height h. Thus, as far as the dimension of the specimen is concerned, the critical shear force depends not only on the aspect ratio as analyzed by previous investigators [ 1,2,12], but also on the height of the specimen. In other words, both dimensions of the rectangular specimen play a part in determining the critical shear force.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the region of high aspect ratio (r > 3), the change in critical shear ratio caused by the change in D, and D2 is much larger than the caused by the aspect ratio, although at a smaller aspect ratio (r < 2), the change is equally significant. It is important to note that the critical shear force is related to the critical shear ratio through equation 13, which involves the specimen height h. Thus, as far as the dimension of the specimen is concerned, the critical shear force depends not only on the aspect ratio as analyzed by previous investigators [ 1,2,12], but also on the height of the specimen. In other words, both dimensions of the rectangular specimen play a part in determining the critical shear force.…”
Section: Resultsmentioning
confidence: 99%
“…I In the process of tailoring a flat piece of fabric into a three-dimensional surface, shearing must occur. This ability of fabric to deform within its plane is important not only to tailorability [3,8,13], but also to the handle of fabric [5, 61. As the shear stress increases, however, a critical stage is reached where the fabric starts to deform out of its plane, i.e., it buckles.…”
mentioning
confidence: 99%
“…Extensive research conducted since the 1960s has indicated that the more important fabric properties in producing suits and tailored garments with good appearance and stability are fabric weight; bending, shear, and tensile properties; longitudinal compressibility; dimensional stability; and possibly surface frictional characteristics [9,10,11,12,14,18]. Various data charts [ 12] have been developed using different combinations of mechanical properties to define the region in which fabrics would be expected to have good tailoring performance and handle.…”
mentioning
confidence: 99%
“…Many researchers have investigated the relationships between these properties and the mechanical properties of fabric. Lindberg et al 5 and Waesterberg 6 investigated the relationship between the making-up properties of several wool fabrics and the mechanical properties of fabrics such as tensile strain, bending stiffness and shearing. Morooka and Niwa 7 , Shishoo 8 , and Kawabata and Niwa 9 investigated the factors that contribute to the making-up properties and a good appearance in finished garments by measuring the mechanical properties of fabrics, such as extension, bending, shearing, compression, and surface friction.…”
Section: Introductionmentioning
confidence: 99%
“…Relating to garment tailoring, the ability of fabric deformation is called the making-up property, tailorability or formability [5][6][7] . Many researchers have investigated the relationships between these properties and the mechanical properties of fabric.…”
Section: Introductionmentioning
confidence: 99%